134k views
1 vote
Solve the system by elimination

x+3y=5

-x-y=-3

User Bruckwald
by
4.8k points

1 Answer

6 votes

Answer:

x = 2 y= 1

Explanation:

Solve the system by elimination by stacking the equations lining up the variables.

x + 3y = 5

-x - y = -3

Next, add each of the like terms.

x + 3y = 5

+ -x - y = -3

-----------------------

0x + 2y = 2

y = 1

Then substitute y = 1 into one of the equations.

x + 3(1) = 5

x + 3 = 5

x = 2

User Alexndm
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.